INTEGUMENTARY AND VISCERAL EPIDEMIOLOGICAL PROFILE OF LEISHMANIASIS IN MONTES CLAROS COUNTY - Fabricio Xavier Oliveira Pinheiro; Victoria Liery Ribeiro Alves; Yure Batista de Sousa; Mirela Lopes Figueiredo; Ana Augusta Maciel de Souza; Patrícia Fernandes Prado (PsychTech & Health Journal)
The present study aims to describe the epidemiological profile American Integumentary Leishmaniasis (LTA)and Visceral Leishmaniasis (LV) in the Montes Claros/MG population between 2016 to 2020. The study is based on documentary research adopting a quantitative. The data was gathered from the electronic Notifiable Diseases Information System (SINAN - Sistema de Informações de Agravos de Notificação. Results showed that 457 notifications were registered, 328 cases of ATL, and 129 cases of VL. The profile of the public affected by both diseases was mainly male, aged between 20 to 59 years, who have incomplete elementary education and declared to be brown. The data allows concluding that ATL shows a constant increase in cases, whereas VL has been reducing its incidence. Thus, it is necessary to strengthen and expand the disease control policies since it is a historically endemic region with a high number of cases in recent years.